Consequences Of Police Investigations for Investigation Errors That Cause Someone to Become a Suspect/Defendant - Suwarto, Suwarto (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The police who serve as investigators carry out the investigation process and the police who serve as investigators carry out the investigation. The process of inquiry and investigation is a very important thing in criminal procedural law, because in its implementation it often has to touch on the degree and/or dignity of the individual under suspicion, therefore one of the important mottos in criminal procedural law is that the essence of investigating criminal cases is to to clear up the problem, to pursue the perpetrator of the crime, while preventing innocent people from acting inappropriately. Regarding the authority of investigators, of course there are efforts that can be made by the reported party if he has been named a suspect or other efforts that can be taken by the reported party if an Inquiries/investigation error occurs.